Table of Content - -, (Journal of agricultural, environmental and veterinary sciences, 2024)
Table of Content:1. Molecular Weight Determination of L-asparaginase from Bacillus licheniformisDr. Vivian Ramzi Daifallah, Dr. Sabah Nassib Yazji, Dr. Lina Abdulkarim Al-Amir2. Environmental Toxins and Their Organ-Specific Effects: A Comprehensive Review of Human Exposure and AccumulationDr. Emam Atiyah Ibadi, Mr. Hussein Kamil Awad, Ms. Lujain Ibrahim Hussain
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences